Race and Gender Discriminatory Utterance through Speech Acts in Hidden Figures Movie 2016: English - Siti Alkhaerani; Ruminda; Erfan Muhammad Fauzi (Prodi Tadris Bahasa Inggris, 2025)
Discrimination refers to the unfair treatment of individuals or groups based on characteristics such as race, nationality, religion, or social class. This social issue often arises due to differences in race, nationality, religion, and social class. This study analyzes the types of speech acts that reflect discrimination in the 2016 film Hidden Figures. The research aims to identify the types of speech acts and the meanings behind the discriminatory utterances appears in the Hidden Figures movie. The study adopts a qualitative method with a pragmatic approach, utilizing Searle’s speech act theory. According to Searle, speech acts can be categorized into five types: representatives, directives, commissives, expressives, and declarations. The data collection process involves observing the movie, understanding the plot, and taking notes of utterances that contain race and gender discrimination. As the result, this research reveal 15 discriminatory utterances categorized as representative speech acts, one utterance categorized as a directive speech act, one utterance as a commissive speech act, two as expressive speech acts, and one as a declaration speech act. These findings were obtained from the dialogues between the three main characters and other characters. The characters who more frequently exhibited discriminatory utterances were those holding higher positions than the three main characters. Using a pragmatic approach, this research also analyzes the meaning contained within the discriminatory utterances identified in the data. These results provide insight into how discriminatory language manifests in movie dialogue and the types of speech acts used to convey race and gender discrimination.